The Correlation of PD-L1 Overexpression With Tumor Budding In Cervical Carcinoma - Lestari, Desak Putu Oki; Analysa, Analysa; Armerinayanti, Ni Wayan; Riasa, I Nyoman Putu; Artha, I Gusti Alit (http://dharmais.co.id/, 2024)
Background: Several studies have proven the relationship between PD-L1, which is known as an immunotherapy target, and poor prognosis. The presence of a tumor budding (TB) group tumor outside the main tumor is also associated with a poor prognosis. The purpose of this study was to determine the relationship between PD-L1 and the grade of TB in cervical carcinoma. Methods: The design of this research is a case-control study with a retrospective approach. The sample is from a paraffin block of the primary cervical cancer tumor from the results of surgery in Balimed Denpasar Hospital between 2020 and 2023. From the statistical formula for the case-control study, a minimum sample of 15 is obtained for the case group with the criteria of high-grade TB, while 15 people were in the control group with low-grade TB. Immunohistochemistry (IHC) PD-L1 is positive if the membrane or cytoplasm is brown, and is negative if there is no brown color on the membrane or cytoplasm. Inferential statistics were used to evaluate the relationship between PD-L1 overexpression and low- and high-grade TB in cervical carcinoma using a chi-square test. Results: The results of this research revealed (p = 0.273) that there was no correlation between PD-L1 expression and high- and low-grade TB. Overexpression of PD-L1 was associated with a 2.250-fold increased risk of high-grade TB (OR = 2.250 with a 95% confidence interval of 0.103–1.915). Conclusions: The severity of TB does not correlate with PD-L1 expression. The functions of PD-L1 and other variables in the carcinogenesis of TB development are the cause of this weak association.